Genome-wide analyses provide insights into genetic variation, phylo- and co-phylogenetic relationships, and biogeography of the entomopathogenic nematode genus Heterorhabditis - Ricardo A.R. Machado; Arthur Muller; Alexandre Hiltmann; Aashaq Hussain Bhat; Vladimír Půža; Antoinette P. Malan; Carlos Castaneda-Alvarez; Ernesto San-Blas; Larry W. Duncan; David Shapiro-Ilan; Javad Karimi; Lalramliana; et al. (Molecular Phylogenetics and Evolution, 2025)

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

Hyperpalatable Diet and Physical Exercise Modulate the Expression of the Glial Monocarboxylate Transporters MCT1 and 4 - Luis V. Portela; Andressa W. Brochier; Clarissa B. Haas; Afonso Kopczynski de Carvalho; Jussania A. Gnoato; Eduardo R. Zimmer; Eduardo Kalinine; Luc Pellerin; Alexandre P. Muller (Molecular Neurobiology, 2017)

Brain Insulin Administration Triggers Distinct Cognitive and Neurotrophic Responses in Young and Aged Rats - Clarissa B. Haas; Eduardo Kalinine; Eduardo R. Zimmer; Gisele Hansel; Andressa W. Brochier; Jean P. Oses; Luis V. Portela; Alexandre P. Muller (Molecular Neurobiology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.